Study of humidity in box type solar cooker - Wong, S.J.U (University Malaysia Sarawak, UNIMAS., 2005)
Alternative energy is now becoming concerned globally. The energy shortage and problem due to deforest had made people try to exploit renewable energy in order to tackle the problem. Although solar cooker is still not common but it had been proved that it can be a good tool if it is well designed and constructed.